2012
DOI: 10.1597/10-145
|View full text |Cite
|
Sign up to set email alerts
|

Application of the International Classification of Functioning, Disability, and Health–Children and Youth Version (ICF-CY) to Cleft Lip and Palate

Abstract: Adopting International Classification of Functioning, Disability, and Health: Children and Youth Version domains in cleft lip and/or palate may aid experts in identifying appropriate starting points for assessment, counseling, and therapy. When used as a clinical tool, it encourages health care professionals to go beyond treatment and outcome perspectives that are focused solely on the child and to include the children's environment and their familial/societal context. In order to establish improved, evidence-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 186 publications
(167 reference statements)
1
38
0
1
Order By: Relevance
“…Contextual factors relate to environmental and personal factors. The Children and Youth Version (ICF-CY, 2007) was derived from ICF, specifically designed to take the changing nature of children's health and development into account (McGormack et al, 2010;Neumann & Romonath, 2012). Cleft speech problems do have a physical basis, but for a wider, more holistic view of the impact of cleft speech impairment, the ICF framework might be helpful to understand the impact on the affected child.…”
Section: International Classification Of Functioning Disability and mentioning
confidence: 99%
“…Contextual factors relate to environmental and personal factors. The Children and Youth Version (ICF-CY, 2007) was derived from ICF, specifically designed to take the changing nature of children's health and development into account (McGormack et al, 2010;Neumann & Romonath, 2012). Cleft speech problems do have a physical basis, but for a wider, more holistic view of the impact of cleft speech impairment, the ICF framework might be helpful to understand the impact on the affected child.…”
Section: International Classification Of Functioning Disability and mentioning
confidence: 99%
“…In a global expert survey to develop an ICF core set for children with cerebral palsy who are younger than six years of age, the selection of d categories by experts was more than 15% for d3, d4, d5 and d9 chapters [21]. In the cleft lip and/or palate Core Set for children younger than 17 years of age, the selected d categories were in all nine chapters except d4 [34]. For older children (mean age eight years), the most frequent d categories in restriction in dental health were ''Handling stress'' (d2), ''Speaking'' (d3), ''Caring for body parts'' (d5) and ''Looking after one's health'' (d6) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported e categories from the same four chapters [21,24,34]. All studies have addressed the importance of the home environment and services for infants with DD.…”
Section: Discussionmentioning
confidence: 99%
“…Research and clinical practice in patients with cleft lip and/or palate (CL/P) often focuses on the differences in body structures and functions (Neumann & Romonath, 2012). However, according to the International Classification of Functioning, Disability, and Health: Children and Youth Version (ICF-CY), developed in 2007 by the World Health Organization (WHO), other aspects, including activities and participation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…coping style, psychological assets) should not be overlooked (World Health Organisation, 2007). Analysis of these personal factors necessitates assessment of how the esthetic aspects of children with CLP are handled (Neumann & Romonath, 2012). Therefore, the most relevant aspect to determine treatment success is satisfaction with the facial appearance and speech as judged by both patients and parents (Sinko et al, 2005).…”
Section: Introductionmentioning
confidence: 99%